Avaliação do perfil de mutações e resistência aos inibidores de transcriptase reversa e protease em pacientes pediátricos infectados pleo HIV-1 - Tonami, Camila Alves [UNESP] (2014)
Although great progresses lead a decline of the HIV infection in children, the antiretroviral therapy has found obstacles as the resistance emergency. In this context the goal of this study was evaluate to the profile of mutations and genotypic resistance to the Nucleoside Reverse Transcriptase Inhibitors (NRTI), Nonnucleoside Reverse Transcriptase Inhibitors (NNRTI) and Protease Inhibitors (PI) in children assisted in the Pediatric Immunology Ambulatory, Botucatu School of Medicine. Patients (19) were evaluated (16 with therapeutic failure and 3 naïve). Viral RNA was used as source to RT and PR genomic regions genotyping. Subtype B was the most frequent (78.95%) in thi study. The NRTI resistance mutations found were L214F (73.7%), M184V (42.1%), R211K (42.1%), M41L (31.5%), T215Y (31.5%), L210W (21%), V118I (21%). K103N and Y188L were found in 26.3% e 10.5% and we are associated with NNRTI use. About the PI the mutations most frequent were M36I (63.1%), L63P (52.6%), E35D (47.3%), R41K (31.5%), I13V (31.5%), M46V (26.3%), L90M (26.3%), I93L (26.3%), V77I (26.3%), V82A (21.1%), I54V (21.1%). The ARVs resistance analysis showed that 3TC, AZT, EFV and NVP have the lower potential for use due to resistance. PI presented great potential for use due to high genetic barrier. From three naïve patients one presented resistant viral variants to EFV and NVP, suggesting transmitted resistance. New studies should be performed to evaluate these findings